1993
DOI: 10.1136/thx.48.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arterial oxygen desaturation on six minute walk distance, perceived effort, and perceived breathlessness in patients with airflow limitation.

Abstract: Background The effect of exercise induced hypoxaemia in determining submaximal exercise capacity, perceived breathlessness, and perceived exertion is not known. The purpose of this study was to investigate the relation of these variables to the results of lung function tests and the degree of hypoxaemia during submaximal exercise in patients with airflow limitation. Methods Forty two patients with chronic obstructive airways disease and 28 patients with chronic severe asthma were studied. Spirometry was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
4
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 27 publications
8
60
4
1
Order By: Relevance
“…Pa,O 2 f7.32 kPa (55 mmHg) is usually considered clinically significant, and may limit exercise tolerance with the potential to endanger the subject. This is seen in most patients with ILD and PVD, in many patients with moderate and severe COPD [50][51][52][53][54], and less frequently in patients with intracardiac left-to-right shunting or chronic heart failure [4]. Interestingly, it can also be seen in elite endurance athletes (see supplementary material, 1.8).…”
Section: Pulmonary Gas Exchange Abnormalitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Pa,O 2 f7.32 kPa (55 mmHg) is usually considered clinically significant, and may limit exercise tolerance with the potential to endanger the subject. This is seen in most patients with ILD and PVD, in many patients with moderate and severe COPD [50][51][52][53][54], and less frequently in patients with intracardiac left-to-right shunting or chronic heart failure [4]. Interestingly, it can also be seen in elite endurance athletes (see supplementary material, 1.8).…”
Section: Pulmonary Gas Exchange Abnormalitiesmentioning
confidence: 98%
“…Arterial desaturation during exercise is a common feature of advanced COPD [53,54]. While desaturation may occur with any type of intense leg exercise, walking either on a treadmill or freely along the ground elicits more hypoxaemia than cycleergometry [54,[86][87][88].…”
Section: Arterial Oxygen Desaturation During Exercisementioning
confidence: 99%
“…The current study is the first to report that EID during 6MWT is more common in non-survivors, although this was not a significant factor after multivariate analysis. In patients with limited airflow, Mak et al showed that the level of EID during 6MWT was related to the severity of impaired lung function (25). However, impairment of lung function could not be accurately predicted by any single lung function test (25).…”
Section: Correlations Between 6mwt-derived Variables and 6-year Survivalmentioning
confidence: 99%
“…[3][4][5] Yet, their physiological determinants and clinical consequences are still subject of debate. In general, patients with EID are characterized by severe airflow limitation, low diffusing carbon monoxide capacity (DLCO), reduced resting arterial oxygenation [6][7][8][9] and the presence of emphysema [10][11][12] In addition, EID is also related to numerous variables that include the rate of lung function decline and health status 13 , physical activity 14 , and the outcomes of hospitalization as well as mortality.…”
Section: Introductionmentioning
confidence: 99%